Contributions and discussions on the reprint of Oscar Teran's Nuestros años sesenta: La formación de la nueva izquierda intelectual argentina (Quinto Sol, 2013)
The recent reprint of Oscar Terán's Nuestros años sesentas. La formación de la nueva izquierda intelectual argentina by Siglo XXI publishers, generated a propitious moment to reflect on the contribution of the work that was released over twenty years ago now. Quinto Sol, in its Notes and Communications section, considered it important to promote a forum for exchange between different historians, who from different perspectives -generational and historiographical- and from our present, analyzed this key work to understand these time. Essays by Jorge Saab, Monica Gordillo, Vera Carnovale and Sergio Pujol note the value of such work and invite to revisit it. Compilation and editing was conducted by Ana Maria T.Rodríguez, Mary Esther Folco and Laura Sanchez, members of the editorial team of Quinto Sol.